Effects of invasion by introduced versus native conifers on coastal heathland vegetation. (27th November 2012) - Saure, Heidi I.; Vandvik, Vigdis; Hassel, Kristian; Vetaas, Ole R.; Scheiner, Sam
Abstract Questions What are the effects of conifer invasion on plant species composition and richness of coastal heathlands; do effects differ between heathlands invaded by introduced or native coniferous tree species? Location Threatened coastal Calluna heathlands, western Norway. Methods We compared the effects of invasion by introduced Sitka spruce (Picea sitchensis (Bong.) Carr.) and native Scots pine (Pinus sylvestris L.) on heathland plant communities by focusing on the local impacts of single coniferous tree canopies. For each of 58 target coniferous trees (2–4‐m tall), 2‐m transects were laid out in a north and south orientation from the tree stem to beyond the tree canopy, and control transects were laid out in open heathland adjacent to the target trees. Vascular plants and bryophytes were recorded within 0.0625 m2 contiguous quadrats along the transects. Principal response curves (PRC) and generalized linear mixed models (GLMMs) were used to investigate tree canopy effects on species composition and richness. Results Invasion by coniferous trees induced considerable changes in the coastal heathland vegetation: distinct microcommunitites developed beneath the canopies of relatively young, single coniferous trees in the heathlands. There was a marked difference in subcanopy species composition under the introduced Sitka spruce relative to the native Scots pine; forest floor species had colonized to a greater extent under Sitka spruce, replacing the light‐demanding species characteristic of the coastal heathland vegetation. Conclusion Our study showed that conifer invasion induces considerable and rapid changes in heathland vegetation, and that the effects were stronger under the introduced conifer. This suggests that Sitka spruce invasion may pose a more immediate threat to the characteristic coastal heathland vegetation and flora than succession based on native conifers. The open coastal heathlands along the Atlantic coast of Western Europe are a threatened landscape of high conservation value, and our results suggest that the spread of Sitka spruce into these landscapes should be controlled, especially in heathlands that are targeted for conservation.